Meta-Analysis of Randomized Controlled Trials Comparing Latanoprost with Other Glaucoma Medications in Chronic Angle-Closure Glaucoma. Issue 1 (January 2015) - Li, Jingjing; Lin, Xiaoti; Yu, Minbin
Purpose: To evaluate the efficacy and safety of latanoprost compared with other glaucoma medications in the treatment of chronic angle-closure glaucoma (CACG) and to provide the basis for clinical medication. Methods: Major literature databases were searched for randomized controlled trials (RCT) involving latanoprost among patients with CACG. Primary outcome measures were absolute changes in intraocular pressure (IOP) and incidence of ocular adverse events. Statistical analyses included the calculation of standardized mean difference (SMD) and relative risk (RR). The statistical analysis was performed using STATA version 12.0 software. Results: Ten RCT involving 1096 patients were included in this meta-analysis. Analysis showed that latanoprost was not significantly different from other glaucoma medications in reducing IOP (SMD = 0.29, 95% confidence interval [CI] −0.02 to 0.59, p=0.069). Further subgroup analysis revealed that latanoprost was superior compared with timolol (SMD = 0.64, 95% CI 0.46 to 0.82, p<0.001) and marginally inferior to travoprost and bimatoprost (SMD = −0.19, 95% CI −0.35 to −0.02, p = 0.026). As for conjunctival hyperemia, latanoprost caused a higher proportion than timolol (RR = 2.36, 95% CI 1.27 to 4.37, p = 0.007). However, latanoprost was associated with lower incidence of conjunctival hyperemia (RR = 0.42, 95% CI 0.30 to 0.59, p<0.001), and with fewer occurrence of other ocular side effects (excluding conjunctival hyperemia) than travoprost and bimatoprost (RR = 0.61, 95% CI 0.48 to 0.78, p<0.001). Conclusions: Travoprost and bimatoprost are superior in IOP control than latanoprost, but latanoprost is better tolerated in patients with CACG.